Toleransi dan Diskursus Post-Sekularisme - Otto Gusti Madung (Jurnal Ledalero, 2016)
This essay presents two types of tolerance: passive tolerance and active or authentic tolerance. Passive tolerance is vertical and is illustrated in the attitude of one being forced by a pluralist societal situation to allow others to exist. Here tolerance is a gift from the powerful majority but can be taken away at any time if minorities infringe a number of conditions. Active or authentic tolerance accepts the right to existence, freedom and the wish of others to develop precisely as others. This principle of tolerance is in accord with the situation of contemporary democratic societies that are plural and which are characterized by potential conflict due to differing concepts of the good life. This essay illustrates how the concept of authentic tolerance is an appropriate model for a post-secular society marked by an increasingly public function by religion. Keywords: Passive tolerance, active tolerance, secularization, postsecularism,public reason,religion --------------------------------------------------------------------------------------------------------------------------- Tulisan ini memperkenalkan dua jenis toleransi yakni toleransi pasif dan toleransi aktif atau autentik. Toleransi pasif bersifat vertikal dan tampak dalam sikap terpaksa membiarkan yang lain hidup karena realitas sosial yang plural. Di sini toleransi adalah hadiah dari penguasa dan setiap saat dapat dicabut kembali jika kaum minoritas melanggar sejumlah ketentuan. Toleransi aktif atau autentik mengiakan hak hidup atau keberadaan, kebebasan dan kehendak yang lain sebagai yang lain untuk berkembang. Prinsip toleransi ini sesuai dengan kondisi masyarakat demokratis dan plural kontemporer yang diwarnai potensi konflik lantaran perbedaan konsep good life. Tulisan ini akan menunjukkan bahwa konsep toleransi autentik merupakan konsep yang cocok dengan kondisi masyarakat post-sekular yang ditandai dengan menguatnya peran publik agama- agama. Kata-kata kunci: Toleransi pasif, toleransi aktif, sekularisasi, postsekularisme,nalar publik, agama